1991
DOI: 10.1111/j.1365-2222.1991.tb01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal IgE: a poor screen for atopic disease

Abstract: Screening for atopic disease using neonatal serum IgE has been advocated on the basis of the predictive value of elevated levels. However, this is only one measure of validity. The test was validated fully in 92 infants with a bi-parental history of atopy using 0.7 IU/ml as the cut-off. All infants were assessed prospectively for evidence of atopic disease (eczema, recurrent wheezing or food reactions) and skin-prick test positivity in the first year. Total serum IgE was measured by ultrasensitive ELISA on 61 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 16 publications
3
41
0
1
Order By: Relevance
“…Atopic mothers, in contrast, were reported to modify the development of the infant’s immune response towards the allergic phenotype [10, 11]. However, this was attributed mainly to transplacental exposure to maternal antibodies and cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atopic mothers, in contrast, were reported to modify the development of the infant’s immune response towards the allergic phenotype [10, 11]. However, this was attributed mainly to transplacental exposure to maternal antibodies and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of atopy at the chromosome locus 11q was shown to be detectable only through the maternal line [10, 11]. These studies suggest that an atopic mother can modify the development of the infant’s immune response towards the allergic phenotype, possibly by factors experienced by the fetus in utero.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This finding may suggest that our children experience increased susceptibility to intrauterine factors (e.g., T helper 2, IL-4 or IL-13, cytokine production, allergen exposure, maternal lifestyles) suspected of increasing isotype class switching to IgE in utero[21]. But in general, the independent predictive value of cord blood IgE for risk of allergy or asthma remains unconvincing in most [22,23,24], but not all [25, 26], studies. Our results in the inner-city population do not support an association between increased cord blood IgE and increased risk of early respiratory disease including asthma, possibly diminishing its clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…The human fetus appears to produce IgE, but at relatively low levels. Nonetheless, higher total IgE levels in cord blood (>0.8 kU/ liter) have been observed and were associated with increased risk for atopic disease in infancy, including atopic dermatitis (98,99), and urticaria from food allergy (100), but the majority of studies have found little predictive value of cord blood IgE on asthma or asthmatic symptoms (98)(99)(100)(101)(102)(103)(104)(105)(106)(107) because of the low sensitivity and predictive value of IgE (98,102,(107)(108)(109). However, none of the studies of the predictive value of cord blood IgE has been conducted among subjects with any substantial understanding of their genetic polymorphisms, examples of which have just been described, or a detailed examination of their residential aeroallergen exposure, reviewed below.…”
Section: Intrauterine Risk Factors For Atopy and Asthma Developmentmentioning
confidence: 99%